2022
DOI: 10.3390/ijms232416184
|View full text |Cite
|
Sign up to set email alerts
|

Advances in NURR1-Regulated Neuroinflammation Associated with Parkinson’s Disease

Abstract: Neuroinflammation plays a crucial role in the progression of neurodegenerative disorders, particularly Parkinson’s disease (PD). Glial cell activation and subsequent adaptive immune involvement are neuroinflammatory features in familial and idiopathic PD, resulting in the death of dopaminergic neuron cells. An oxidative stress response, inflammatory mediator production, and immune cell recruitment and activation are all hallmarks of this activation, leading to chronic neuroinflammation and progressive neurodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 215 publications
1
11
0
Order By: Relevance
“…Myelo-peroxidase, an oxidant-producing enzyme that might harm dopamine neurons, is released by astrocytes, and it has been suggested that astrocytes could control microglial multiplication by releasing the cytokine granulocyte macrophage colony-stimulating factor (GM-CSF) [ 34 ]. By contrast, the marked and considerable increase in microglial activation was already consistently seen in PD animal models and Parkinson’s disease postmortem investigations or MPTP-induced parkinsonism [ 35 , 36 , 37 ]. This stimulation and expansion of microglia is known as the neuroinflammatory characteristic of Parkinson’s disease.…”
Section: Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelo-peroxidase, an oxidant-producing enzyme that might harm dopamine neurons, is released by astrocytes, and it has been suggested that astrocytes could control microglial multiplication by releasing the cytokine granulocyte macrophage colony-stimulating factor (GM-CSF) [ 34 ]. By contrast, the marked and considerable increase in microglial activation was already consistently seen in PD animal models and Parkinson’s disease postmortem investigations or MPTP-induced parkinsonism [ 35 , 36 , 37 ]. This stimulation and expansion of microglia is known as the neuroinflammatory characteristic of Parkinson’s disease.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Other researchers have elucidated and broadened the concept of neuroinflammation in Parkinson’s disease. TNF-alpha (tumor necrosis factor alpha), IL-1, IL-2, IL-4, IL-6, epidermal growth factor (EGF), converting growth factor alpha (TGF-alpha), TGF-1, and TGF-2 have been recognized at elevated levels in nigrostriatal areas of the CNS and ventricular cerebrospinal fluid of Parkinson’s disease patients, supposedly emerging from activated microglia [ 37 , 39 , 40 ]. Neuronal damage may need prolonged exposure to proinflammatory cytokines such as IL-1, according to one theory [ 41 ].…”
Section: Parkinson’s Disease and Microglia: A Look At Their Involvementmentioning
confidence: 99%
“…43 Although there are many reports that the EP1 receptor is neurotoxic and is involved in neurodegeneration through different mechanisms, it has also been found that the EP1 receptor is involved in the upregulation of Nur-related factor 1 (Nurr1) and regulates cell survival and proliferation. 44 Nurr1 plays an important function in the development and maintenance of midbrain DA neurons. 44 PGE2-activated EP1 stimulates Rho leading to the dissociation and activation of PKAc from multiprotein complex I-κB/nuclear factor-κB (NF-κB)/PKAc by phosphorylating I-κB.…”
Section: Pdmentioning
confidence: 99%
“…44 Nurr1 plays an important function in the development and maintenance of midbrain DA neurons. 44 PGE2-activated EP1 stimulates Rho leading to the dissociation and activation of PKAc from multiprotein complex I-κB/nuclear factor-κB (NF-κB)/PKAc by phosphorylating I-κB. Activated PKAc then phosphorylates NF-κB and cyclic AMP response element-binding protein (CREB), resulting in increased expression of Nurr1 at the transcriptional and translational levels 45 (Figure 3).…”
Section: Pdmentioning
confidence: 99%
“…As a transcription factor, Nurr1 plays a crucial role in the development of dopaminergic neurons and contributes to the activation of neuroprotective and anti-inflammatory pathways [ 28 ]. Dysfunction or reduced expression of Nurr1 has been associated with impaired energy metabolism, mitochondrial dysfunction, and oxidative stress [ 29 , 30 ]. Given the association between reduced Nurr1 expression and these changes in dopaminergic neurons, beside anti-synucleinopathy therapy, increasing Nurr1 expression has been suggested as a promising therapeutic target for Parkinson disease [ 28 ].…”
Section: Introductionmentioning
confidence: 99%